FRI0170 Cardiovascular risk factors and disease characteristics are consistently associated with arterial stiffness in rheumatoid arthritis. (15th June 2017) - Gunter, S; Robinson, C; Norton, G; Woodiwiss, A; Tsang, L; Millen, A; Dessein, P
Abstract : Background: In the non-rheumatoid arthritis (RA) population, arterial stiffness contributes to cardiovascular disease risk beyond brachial blood pressure and other established cardiovascular risk factors. The increased cardiovascular disease risk in RA is now well documented. In this regard, how RA impacts on arterial stiffness remains uncertain. Objectives: The aim of the present study was to identify potential determinants of comprehensively assessed arterial stiffness in a relatively large group of ethnically diverse patients with RA. Methods: Relationships of traditional cardiovascular risk factors and RA characteristics with 9 arterial stiffness markers including central systolic and pulse pressure, pulse wave velocity, augmentation index, forward and reflected wave pressure, reflection magnitude, brachial-to-aortic pulse pressure amplification (a marker of reduced wave reflection) and peripheral pulse pressure were identified in multivariable backward regression models among 177 (118 white, 32 Asian, 22 black, 5 mixed ancestry) patients without established cardiovascular disease. Results: Recorded characteristics explained 37% (pulse wave velocity) to 71% (reflected wave pressure) of the variability in arterial stiffness. RA duration (partial r=0.17, p=0.04), rheumatoid factor status (partial r=-0.19 to 0.20, p=0.01 to 0.03), leukocyte counts (partial r=0.16 to 0.19, p=0.02 to 0.05) and total cholesterol (-0.18 to 0.26, p=0.00 to 0.03) were associated with enhanced central systolic blood pressure or/and wave reflection markers. C-reactive protein (partial r=-0.24, -0.17 and -0.20, respectively, p≤0.05) was paradoxically related to reduced central pulse pressure, pulse wave velocity and forward wave pressure, and body mass index (partial r=-0.39 to 0.42, p=0.00 to 0.02) and insulin resistance (partial r=-0.21 to -0.20, p=0.00 to 0.01) to reduced wave reflection and peripheral pulse pressure. Exercise (partial r=0.19, p=0.02) and alcohol (partial r=-0.27, p=0.00) consumption were associated with increased pulse pressure amplification and decreased peripheral pulse pressure, respectively. Tumour necrosis factor-α inhibition (partial r=-0.25, p=0.00) was related to reduced pulse wave velocity and tetracycline use (partial r=-0.20, p=0.02) to reduced peripheral pulse pressure. Conclusions: Traditional cardiovascular risk factors and disease characteristics are consistently associated with vascular hemodynamic alterations in RA. The role of arterial stiffness in cardiovascular disease risk in RA needs further study. Disclosure of Interest: None declared